Green Strategic Leadership and Sustainability Reporting: Bridging Corporate Practice with the SDGs - Muhammad Yamin Nochh (Golden Ratio of Data in Summary, 2026)
This study examines the role of green strategic leadership in shaping the quality, integrity, and SDG alignment of corporate sustainability reporting. The research aims to clarify how leadership vision, organizational culture, governance structures, and institutional pressures collectively influence the depth and authenticity of sustainability disclosures in the contemporary global sustainability landscape. Employing a qualitative research design grounded in a systematic literature review, this study synthesizes theoretical and empirical findings from recent scholarly work to explore the mechanisms through which leadership affects sustainability reporting practices. The analysis incorporates peer-reviewed sources, conceptual frameworks, and evidence-based insights to construct an integrated understanding of the leadership–reporting nexus. The results indicate that green strategic leadership significantly enhances sustainability reporting by fostering long-term environmental vision, cultivating sustainability-oriented culture, strengthening governance systems, and promoting constructive responses to institutional pressures. Leaders with strong environmental values drive organizations toward more substantive and SDG-oriented disclosures, while governance structures shaped by leadership reduce tendencies toward symbolic reporting and greenwashing. The findings further reveal that leadership plays a mediating role in translating global sustainability expectations into organizational practice, enabling firms to use reporting as a strategic tool rather than a compliance obligation. Overall, the study demonstrates that sustainability reporting excellence is inseparable from the quality of leadership guiding corporate sustainability strategy..